The Effect of Endurance Training on Blood Lactate Concentration and Anaerobic Threshold in Bangladeshi Female Handball Athletes - Shanta, Sharmin Akter; Ajita (Physical Education Theory and Methodology, 2025)
Background. Endurance training has an essential role in improving the aerobic capacity and postponing the onset of exhaustion that can be beneficial to enhancing the performance. Handball involves both aerobic and anaerobic energy systems in the human body. Therefore, it becomes crucial to comprehend how training influences physiological variables such as anaerobic threshold and blood lactate concentration. Objectives. The objective of this study was to examine the effect of an endurance training program on anaerobic threshold and blood lactate concentration in Bangladeshi female handball players. Materials and methods. A total of sixty-four female athletes were selected using a purposive random sampling technique. The participants were randomly divided into two groups: 32 in the experimental group and 32 in the control group. A blood lactate analyzer, pulse oximeter, and treadmill test according to the Bruce protocol were used to assess blood lactate concentration, anaerobic threshold, resting heart rate, and maximum heart rate. Results. The study observed a significant improvement in the experimental group, including a reduction in resting blood lactate concentration from 1.72 ± 0.15 mmol/L to 1.42 ± 0.12 mmol/L at the post-training phase. Additionally, there was an increase in onset of blood lactate accumulation from 4.51 ± 0.26 mmol/L to 4.73 ± 0.15 mmol/L, and an increase in speed at lactate threshold from 7.0 ± 0.0 km/h to 7.49 ± 0.19 km/h. It was also noted a considerable enhancement in the control group for variables such as resting heart rate, maximum heart rate, resting blood lactate concentration, and peak lactate concentration due to regular handball participation. Cohen’s d was calculated to determine the effect size of endurance training. An independent t-test also revealed substantial differences between the experimental and control groups (p < 0.05). Conclusions. The findings of this study indicate a significant effect of endurance training on the anaerobic threshold and blood lactate concentration in Bangladeshi female handball players.